Union of Comoros : Request for a Staff-Monitored Program-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2021)
Comoros is a small, fragile island state (population: 850,000) with persistently low and shock-prone growth. The last Article IV Consultation (completed in early 2020) assessed Comoros' fragility as arising from two vicious circles: economic fragility manifests in low fiscal revenue, insufficient government investment in human and physical capital, and pronounced vulnerability to shocks; while institutional fragility manifests in governance challenges, low government implementation capacity, and a weak judicial system. The circles feed into each other, undermining economic performance and stability. Overcoming fragility requires breaking both circles.